INFLUENCE OF DIFFERENT ESTRUS SYNCHRONIZATION PROTOCOLS ON FERTILITY AND PLASMA PROGESTERONE IN ANOESTRUS CROSSBRED COWS - BUHECHA, K V; DHAMI, A J; HADIYA, K K; PATEL, M D; PARMAR, S C; KILLEDAR, A (The Indian Journal of Animal Reproduction, 2023)
A study was carried out to evaluate the clinical response and monitor the peripheral plasma progesterone profile in 46 postpartum anoestrus crossbred cows(>90 days) treated with standard hormonal protocols Triu-B/ PRID, Ovsynch and Heatsynch(n=12 each), keeping untreated anoestrus control (n=10) group and the results were compared with normal cyclic control (n=1 0)group. All the cows(100 %) under three protocols exhibited estrus within mean intervals of 67.00±1.74, 69.83±0.87 and 68.17±1.24 h, respectively, from PGF2a injection. The conception rates obtained at induced estrus in cows under Triu-B, Ovsynch and Heatsynch protocols were 33.33, 41.66and 33.33 %, respectively. The corresponding overall conception rates of three cycles were 50.00, 58.33 and 41.66%, respectively.In untreated anoestrus control group, only 2 cows (20 %) expressed spontaneous estrus with overall conception rate of 20.00%. In normal cyclic control group the conception rates at first cycle and overall of 3 cycles were 40.00 and 60.00%, respectively.The overall mean plasma progesterone concentrations (ng/ml) found in true anoestruscows on day 0, 7, 9/10 (Al) of treatment and on day 21 post-Al were 0.85±0.21, 4.80±0.31, 0.58±0.11 and 3.97±1.14, respectively,underTriU-B protocol; 0.58±0.11, 4.55±0.28, 1.33±0.48 and 4.03±1.32 under Ovsynch protocol and 0.81±0.22, 5.11±0.75, 0.43±0.06 and 3.10±1.06under Heatsynch protocol.The values on day 7 of treatment and day 21 post-Al were significantly (P<0.01) higher than other two periods (day of initiation of treatment, and day of estrus/FTAI) in all three groups. The mean plasma progesterone concentrations (ng/ml) were significantly (P<0.01) higher in conceived than nonconceived cows on day 21 post-Al in normal cyclic control cows (6.49±0.39 vs. 1.15±0.30),in Triu-8(6.95±0.24 vs. 0.99±0.35),Ovsynch(8.35±0.85 vs. 1.43±0.40)and Heatsynch protocol(6.06±0.78 vs. 1.33±0.92).AII the three hormonal protocols used in anoestrus cows resulted into 100% estrus induction and good conception rates particularly with Ovsynch followed by Triu-B suggestive of better scope for their use under field conditions.